A new species of Sandro Karaman & Barnard (Crustacea: Amphipoda: Austroniphargus family group) from South-East Madagascar - Daneliya, Mikhail E. (Zootaxa, 2011)
A new austroniphargid amphipod Sandro straussi sp. n. (Crustacea, Amphipoda, Austroniphargus family group) is described on a large collection from forest streams of the Ranomafana National Park, South-East Madagascar. The new species differs from the only known congener, S. starmuehlneri (Ruffo, 1960), by the absence of dorsal spine-setae on telson, unlobed propodus of gnathopods, presence of distal bifurcation on posterior lobe of male uropod 3 peduncle and other characters. The unique feature of S. straussi sp. n. is the sexual dimorphism of uropods 1 and 3: males of the species possess a distolateral lobe on the uropod 1 peduncle and mentioned bifurcated lobe on uropod 3. Despite the absence of eyes, S. straussi sp. n. is widely distributed in epigean stream of the Ranomafana National Park. The diagnosis of the genus Sandro Karaman & Barnard, 1979 is revised and a key to austroniphargid species is composed.